Factors associated with a maternal lower‐limb neurological deficit after vaginal delivery. (12th October 2022) - Tournier, Alexane; Doremieux, Anne Cecile; Drumez, Elodie; Labreuche, Julien; Cassim, François; Gonzales, Max; Garabedian, Charles; Subtil, Damien
Abstract: Introduction: The etiology of lower‐limb neurological deficit after vaginal delivery remains poorly understood. The objective herein was to identify factors associated with this maternal nerve injury after vaginal delivery. Material and methods: A single‐center, case–control (matching 1:4) study. Cases were women with a lower‐limb neurological deficit that appeared immediately after vaginal delivery. Controls were randomly selected women who gave birth vaginally during the same period, without any deficit. Finally, to assess the rates of factors associated with these deficits, we studied them using a randomly selected 5% sample of the population with vaginal deliveries. Results: During the 30‐month study period, 31 cases were identified among 10 333 women who gave birth vaginally (0.3%, 95% CI 0.20–0.43); 124 controls were also included. After logistic regression, the presence of a neurological deficit after delivery was associated with second‐stage labor duration (per hour odds ratio [OR] 3.67, 95% CI 2.09–6.44; OR per standard deviation increase 2.73, 95% CI 1.75–4.25, p  < 0.001) and instrumental delivery (OR = 3.24, 95% CI 1.29–8.14, p  = 0.012), with no interaction effect ( p  = 0.56). Extrapolation of these factors to a 5% sample of the overall population of women with vaginal births showed that the rate of these deficits would be very low for women with second‐stage labor lasting up to 90 min without instrumental delivery (0.05%) but increased to 1.52% when these factors were combined (OR 33.1, 95% CI 9.4–116.9). Conclusions: Following vaginal delivery, the onset of a neurological deficit is principally associated with the duration of second‐stage labor and instrumental delivery. Abstract : Maternal nerve injury is associated with second‐stage labor duration and instrumentation. These data may support limiting prolonged second‐stage labor.